Visual forms of gaming practices in online forums daily life - Burak, Tatsiana V. (Journal of the Belarusian State University. Sociology, 2019)
The interpretation of Internet forums everyday life as a communicative game and generalized characteristics and social functions of gaming practices are discussed in the system of forum usersʼ interactions. In connection with the increased need for visualization and maintaining the trust of direct interaction in virtual communication the object of research is the game with visual signs, implemented in the design of photorepresentation. The relationship between the values and elements of travel photographs, travel images of traveler and «alien» everyday life is described on the basis of theoretical analyzing the sign structure of visual texts in everyday communication.